2024
DOI: 10.1038/s41538-023-00245-8
|View full text |Cite
|
Sign up to set email alerts
|

Positive and negative aspects of bacteriophages and their immense role in the food chain

Soniya Ashok Ranveer,
Vaishali Dasriya,
Md Faruque Ahmad
et al.

Abstract: Bacteriophages infect and replicate inside a bacterial host as well as serve as natural bio-control agents. Phages were once viewed as nuisances that caused fermentation failures with cheese-making and other industrial processes, which lead to economic losses, but phages are now increasingly being observed as being promising antimicrobials that can fight against spoilage and pathogenic bacteria. Pathogen-free meals that fulfil industry requirements without synthetic additives are always in demand in the food s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(3 citation statements)
references
References 133 publications
(161 reference statements)
0
3
0
Order By: Relevance
“…The host range of a phage is one of the key qualities to assess its usefulness in phage therapy. The greater the host range within a particular species, the more effective a particular phage will be against the target pathogen causing a specific disease ( Ranveer et al, 2024 ) However, a phage should not have any killing effects on other bacterial species so as not to affect the friendly commensal bacteria. In this regard, the host range of phage MKP-1 attributed to its usefulness as it showed its lytic activity against three strains of Klebsiella but not against any other species.…”
Section: Discussionmentioning
confidence: 99%
“…The host range of a phage is one of the key qualities to assess its usefulness in phage therapy. The greater the host range within a particular species, the more effective a particular phage will be against the target pathogen causing a specific disease ( Ranveer et al, 2024 ) However, a phage should not have any killing effects on other bacterial species so as not to affect the friendly commensal bacteria. In this regard, the host range of phage MKP-1 attributed to its usefulness as it showed its lytic activity against three strains of Klebsiella but not against any other species.…”
Section: Discussionmentioning
confidence: 99%
“…A negative correlation (−0.692) between the content of vitamin C and the number of viable viral particles of bacteriophage phi6 was determined. The antiviral potential of ascorbic acid and low pH was described previously [37,38]. Ascorbic acid is a crucial vitamin for the correct functioning of the immune system of organisms.…”
Section: Antiviral Potential Of Fruit Extractsmentioning
confidence: 99%
“…No repressors or integrases were found in the genome through all annotation tools, con rming Psxφ15 as a virulent phage. Temperate phages are not recommended for biocontrol as these viruses additionally possess the lysogenic cycle, which may confer evolutionary advantages to the bacterial host through the transfer of bene cial genes [32,33]. The annotation tools also revealed that there are 10 tRNA genes in the genome of Psxφ15.…”
mentioning
confidence: 99%